Development of Long-Term Stability of Enveloped rVSV Viral Vector Expressing SARS-CoV-2 Antigen Using a DOE-Guided Approach - MD Faizul Hussain Khan; Caroline E. Wagner; Amine A. Kamen (Vaccines)
Liquid formulations have been successfully used in many viral vector vaccines including influenza (Flu), hepatitis B, polio (IPV), Ebola, and COVID-19 vaccines. The main advantage of liquid formulations over lyophilized formulations is that they are cost-effective, as well as easier to manufacture and distribute. However, studies have shown that the liquid formulations of enveloped viral vector vaccines are not stable over extended periods of time. In this study, we explored the development of the liquid formulations of an enveloped recombinant Vesicular Stomatitis Virus (VSV) expressing the SARS-CoV-2 spike glycoprotein. To do so, we used a design of experiments (DOE) method, which allowed us to assess the stability dynamics of the viral vector in an effective manner. An initial stability study showed that trehalose, gelatin, and histidine were effective at maintaining functional viral titers during freeze–thaw stress and at different temperatures (−20, 4, 20, and 37 °C). These preliminary data helped to identify critical factors for the subsequent implementation of the DOE method that incorporated a stress condition at 37 °C. We used the DOE results to identify the optimal liquid formulations under the selected accelerated stress conditions, which then guided the identification of long-term storage conditions for further evaluation. In the long-term stability study, we identified several liquid formulations made of sugar (sucrose, trehalose, and sorbitol), gelatin, and a histidine buffer that resulted in the improved stability of rVSV-SARS-CoV-2 at 4 °C for six months. This study highlights an effective approach for the development of liquid formulations for viral vector vaccines, contributing significantly to the existing knowledge on enveloped viral vector thermostability.